Stem cell tracking using iron oxide nanoparticles - Bull E (Dove Medical Press, 2014)
Elizabeth Bull,1 Seyed Yazdan Madani,1 Roosey Sheth,1 Amelia Seifalian,1 Mark Green,2 Alexander M Seifalian1,31UCL Centre for Nanotechnology and Regenerative Medicine, Division of Surgery and Interventional Science, University College London, London, 2Department of Physics, King’s College London, Strand Campus, London, UK; 3Royal Free London National Health Service Foundation Trust Hospital, London, UKAbstract: Superparamagnetic iron oxide nanoparticles (SPIONs) are an exciting advancement in the field of nanotechnology. They expand the possibilities of noninvasive analysis and have many useful properties, making them potential candidates for numerous novel applications. Notably, they have been shown that they can be tracked by magnetic resonance imaging (MRI) and are capable of conjugation with various cell types, including stem cells. In-depth research has been undertaken to establish these benefits, so that a deeper level of understanding of stem cell migratory pathways and differentiation, tumor migration, and improved drug delivery can be achieved. Stem cells have the ability to treat and cure many debilitating diseases with limited side effects, but a main problem that arises is in the noninvasive tracking and analysis of these stem cells. Recently, researchers have acknowledged the use of SPIONs for this purpose and have set out to establish suitable protocols for coating and attachment, so as to bring MRI tracking of SPION-labeled stem cells into common practice. This review paper explains the manner in which SPIONs are produced, conjugated, and tracked using MRI, as well as a discussion on their limitations. A concise summary of recently researched magnetic particle coatings is provided, and the effects of SPIONs on stem cells are evaluated, while animal and human studies investigating the role of SPIONs in stem cell tracking will be explored.Keywords: stem cells, nanoparticle, magnetic